Antifungal Activity of Bacillus Species Against Fusarium and Analysis of the Potential Mechanisms Used in Biocontrol - Khan, Noor; Martínez-Hidalgo, Pilar; Ice, Tyler A.; Maymon, Maskit; Humm, Ethan A.; Nejat, Najmeh; Sanders, Erin R.; Kaplan, Drora; Hirsch, Ann M. (Frontiers in Microbiology, 2018)
Fusarium is a complex genus of ascomycete fungi that consists of plant pathogens of agricultural relevance. Controlling Fusarium infection in crops that leads to substantial yield losses is challenging. These economic losses along with environmental and human health concerns over usage of chemicals in attaining disease control are shifting focus towards the use of biocontrol agents for effective control of phytopathogenic Fusarium spp. In the present study, an analysis of the plant growth promoting (PGP) and biocontrol attributes of four bacilli (Bacillus simplex 30N-5, B. simplex 11, B. simplex 237 and B. subtilis 30VD-1) has been conducted. The production of cellulase, xylanase, pectinase and chitinase in functional assays was studied, followed by in silico gene analysis of the PGP-related and biocontrol associated genes. Of all the bacilli included in this study, B. subtilis 30VD-1 (30VD-1) demonstrated the most effective antagonism against Fusarium spp. under in vitro conditions. Additionally, 100 µg/ml of the crude 1-butanol extract of 30 VD-1’s cell free culture filtrate caused about 40% inhibition in radial growth of Fusarium spp. Pea seed bacterization with 30VD-1 led to considerable reduction in wilt severity in plants with about 35% increase in dry plant biomass over the plants growing in Fusarium infested soil. Phase contrast microscopy demonstrated distortions and abnormal swellings in F. oxysporum hyphae on co-culturing with 30VD-1. The results suggest a multivariate mode of antagonism of 30VD-1 against phytopathogenic Fusarium spp., by producing chitinase, volatiles, and other fungal toxic molecules, the characterization of which is underway.